Common variants in the genes of triglyceride and HDL-C metabolism lack association with coronary artery disease in the Pakistani subjects. Issue 1 (December 2017) - Shahid, Saleem; Shabana, N.A.; Cooper, Jackie; Rehman, Abdul; Humphries, Steve
Abstract Background Serum Triglyceride (TG) and High Density Lipoprotein (HDL-C) levels are modifiable coronary artery disease (CAD) risk factors. Polymorphisms in the genes regulating TG and HDL-C levels contribute to the development of CAD. The objective of the current study was to investigate the effect of four such single nucleotide polymorphism (SNPs) in the genes for Lipoprotein Lipase (LPL) (rs328, rs1801177), Apolipoprotein A5 (APOA5) (rs66279) and Cholesteryl ester transfer protein (CETP) (rs708272) on HDL-C and TG levels and to examine the association of these SNPs with CAD risk. Methods A total of 640 subjects (415 cases, 225 controls) were enrolled in the study. The SNPs were genotyped by KASPar allelic discrimination technique. Serum HDL-C and TG were determined by spectrophotometric methods. Results The population under study was in Hardy Weinberg equilibrium and minor allele of SNP rs1801177 was completely absent in the studied subjects. The SNPs were association with TG and HDL-C levels was checked through regression analysis. For rs328, the effect size of each risk allele on TG and HDL-C (mmol/l) was 0.16(0.08) and −0.11(0.05) respectively. Similarly, the effect size of rs662799 for TG and HDL-C was 0.12(0.06) and −0.13(0.0.3) and that of rs708272 was 0.08(0.04) and 0.1(0.03) respectively. The risk allele frequencies of the SNPs were higher in cases than controls, but the difference was not significant (p > 0.05) and SNPs were not associated with CAD risk (p > 0.05). The combined gene score of four SNPs significantly raised TG and lowered HDL-C but did not increase CAD risk. Conclusion The studied SNPs were associated with TG and HDL-C levels, but not with CAD in Pakistani population under study.